Demographic and Clinicopathological Associated Risk Factors in Oral Cancer in Rajasthan: A Retrospective Study - Himanshu Sharma; Sanjay Sharma; Dinesh Yadav; Dinesh Kumar; Mamit Dogra; Jatinder Mohan Arora (Dental Journal of Advance Studies)
Objective: To ascertain the correlation between sociodemographic and clinic-pathological risk variables and oral cancer. Materials and methods: At Mahatma Gandhi Medical College & Hospital (MGMCH) in Jaipur, Rajasthan, India, a two-year cross-sectional survey was conducted. The Medical Records office provided medical records for 300 patients with oral cancer. Results: Males (63.3%), non-smokers (56.6%), betel quid chewers (96.6%), and residents of different sub-cities of Rajasthan made up the bulk of oral cancer cases. The majority of patients were in stages III (30%) and IV (45%) at the time of diagnosis. The most often used type of therapy was a surgical, radiation, or combination. The majority of the patients were still living (73%) at the time of this study. Conclusion: The gingivobuccal sulcus (GBS) complex malignancy was the most frequently involved oral cavity site (33%), and oral squamous cell carcinoma (OSCC) was the most commonly encountered oral cancer in the Rajasthan population (73.3%).